1970
DOI: 10.3329/bvet.v28i1.8812
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of heritability for growth traits of Red Chittagong cattle in a nucleus herd

Abstract: The present study was undertaken to estimate the heritability for growth traits in a nucleus herd of Red Chittagong cattle (RCC) using data from 2005 to 2010. The traits considered were birth weight, weight at three-month intervals from birth to 24 months, and pre-weaning and post-weaning growth rate. The mean pooled weight (mean ± se) of 127 RCC calves from birth to 24 months at three month intervals were 14.7 ± 0.2, 29.3 ± 6.1, 42.6 ± 9.2, 55.0 ± 12.4, 66.2 ± 15.5, 74.5 ± 16.0, 86.1 ± 23.5, 98.8 ± 24.8 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 9 publications
1
12
5
1
Order By: Relevance
“…This result is lower than the results obtained by Afroz et al (2011) found from RCC and Atil et al (2005) found from Holstein calves who found breeding value for birth weight as -3.9438 to 5.8998 and -4.10 to 5.11, respectively. But higher than the results obtained by Alam et al (2007) found from RCC and Shakhawat (2006) found from Pabna Milking as -1.494 to 2.782 and -0.101±0.05, respectively.…”
Section: Growth Traitscontrasting
confidence: 73%
See 4 more Smart Citations
“…This result is lower than the results obtained by Afroz et al (2011) found from RCC and Atil et al (2005) found from Holstein calves who found breeding value for birth weight as -3.9438 to 5.8998 and -4.10 to 5.11, respectively. But higher than the results obtained by Alam et al (2007) found from RCC and Shakhawat (2006) found from Pabna Milking as -1.494 to 2.782 and -0.101±0.05, respectively.…”
Section: Growth Traitscontrasting
confidence: 73%
“…This result is slightly lower than the results obtained by Afroz et al (2011) found from RCC, Rabeya et al (2009) found from RCC, Stamer et al (2004) found from Holstein calves as 0.47 ± 0.06, 0.47 ± 0.06 and 0.50, respectively. Afroz et al (2011) found from RCC, Rabeya et al (2009) found from RCC lower heritability for pre-weaning daily gain of calves compared with the results of present study as 0.48±0.06, 0.50 ± 0.05 and 0.49±0.07, respectively.…”
Section: Heritability (H 2 )contrasting
confidence: 58%
See 3 more Smart Citations